Agnes Nathania PENERAPAN VIRTUAL REALITY TERHADAP DESAIN INTERIOR DI BANDUNG PLANNING GALLERY - Agnes Nathania; Clarine Tiffany (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2020)
In the era of the industrial revolution 4.0., there is already a lot of showroom that uses VR (Virtual Reality). Theexistence of this technology can attract people interest to explore the museum, because it has new andsophisticated elements in it. VR facilities that are increasingly becoming a trend in this museum are used aseducational media and must be accompanied by good implementation to give a good influence as well. Onegallery that has implemented VR facilities in it is the Bandung Planning Gallery. VR facilities in this gallery canvisualize the future of Bandung in 2031 so that people can imagine the future of Bandung. Therefore, thisgallery which is claimed to be a gallery with high technology becomes the object of analysis using qualitativefield observation methods. Through the results of the analysis of the application of VR in this Gallery, theauthors hope that other showrooms can apply VR well in the interior. The implementation of VR will make iteasier for people to learn technology and be ready to face the next era.